The application of modified free inquiry for the science process skills - Yeni Suryaningsih; Iim Halimatul Mu’minah (Universitas Wiralodra, 2022)
This study aimed to improve students' science process skills by applying modified free inquiry, which is a modification of two approaches: guided inquiry and free inquiry. The research method used is true-experimental design. The instruments used are test questions with indicators of science process skills and observation sheets on implementing the modified free inquiry learning model. The data collection technique was descriptive and quantitative with hypothesis testing using a nonparametric test Two Independent Sample Test, the Mann-Whitney test, and the gain score pretest and posttest. The results showed an increase in science process skills with an N-Gain value in the experimental class of 0.87 and the control class of 0.19. The results of hypothesis testing using the Mann-Whitney test obtained a significance value of 0.000 < 0.005, and the observation sheet on the modified free inquiry learning model was obtained 100% well implemented. Based on data analysis, it can be concluded that modified free inquiry can be used as a learning model that can be applied to biology learning and improve science process skills.